Design and fabricate of portable and multifunction shoe rack / Farez Azra’e Arman - Arman, Farez Azra’e (2023)
Shoe racks are common furniture storage units available in the existing market with many various designs. According to study, the most previously existing products are in good working order. In addition, products that provide space or seating but are not portable are provided. Nowadays, most consumers prefer products that provide multi-purpose. The objective of this project is to come up with fresh ideas for making foldable and multi purpose shelves. Furthermore, this project is to create multi-functional and portable shoe racks for everyone’s use especially for students who live in hostel. In this project, I want to use economical, easily accessible material as well as material that could be swiftly manufactured and supervised. In nut shell, this product is designed to assist customers organize their shoes properly and exceed their expectations with a pleasant experience when using it.